Two Earth-size Planets and an Earth-size Candidate Transiting the nearby Star HD 101581 - Michelle Kunimoto; Zifan Lin; Sarah Millholland; Alexander Venner; Natalie R. Hinkel; Avi Shporer; Andrew Vanderburg; Jeremy Bailey; Rafael Brahm; Jennifer A. Burt; R. Paul Butler; Brad Carter; et al. (The Astronomical Journal)
We report the validation of multiple planets transiting the nearby ( d = 12.8 pc) K5V dwarf HD 101581 (GJ 435, TOI–6276, TIC 397362481). This system consists of at least two Earth-size planets whose orbits are near a mutual 4:3 mean-motion resonance, HD 101581 b ( ${R}_{p}={0.956}_{-0.061}^{+0.063}\,R_{\oplus }$ , P = 4.47 days) and HD 101581c ( ${R}_{p}={0.990}_{-0.070}^{+0.070}\,R_{\oplus }$ , P = 6.21 days). Both planets were discovered in Sectors 63 and 64 TESS observations and statistically validated with supporting ground-based follow-up. We also identify a signal that probably originates from a third transiting planet, TOI-6276.03 ( ${R}_{p}={0.982}_{-0.098}^{+0.114}\,R_{\oplus }$ , P = 7.87 days). These planets are remarkably uniform in size and their orbits are evenly spaced, representing a prime example of the “peas-in-a-pod” architecture seen in other compact multiplanet systems. At V = 7.77, HD 101581 is the brightest star known to host multiple transiting planets smaller than 1.5 R _⊕ . HD 101581 is a promising system for atmospheric characterization and comparative planetology of small planets.